QAULLAN LAYYINA SEBAGAI MODEL KOMUNIKASI DI TENGAH MENJAMURNYA UJARAN KEBENCIAN - Khabib Musthofa; Subiono Subiono (Transformatif, 2020)
Hate speech is a lively reprehensible phenomenon on Indonesian social media, the impact of danger if it is not addressed wisely, through its circular related hate speech has been affirmed if hate speech is not handled properly and immediately, it can undermine the principle of the nation and nation with diversity. and protect the diversity of groups in this nation, especially in the era of people who have not fully matured in understanding democracy and difference. The attitude of carrying out hate speech also actually contradicts the ethics of communicating in Islam. One of the communication models taught is by a weak attitude or qaullan layyina. The Qur'an also teaches humans to communicate well, so that a harmonious relationship is created between the messenger and the recipient of the message, and the messages conveyed in the communication can be understood.